2014
DOI: 10.1002/2013jd020159
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurements and modeling of industrial formaldehyde emissions in the Greater Houston area during campaigns in 2009 and 2011

Abstract: A sensitive Mobile differential optical absorption spectroscopy (DOAS) system with real-time evaluation capability and HCHO detection limit of 3 ppb over 100 m has been developed. The system was operated together with a Solar Occultation Flux system for large-scale vertical flux measurements of HCHO, NO 2 , SO 2 , and VOCs in the Houston-Galveston-Brazoria area during two studies, in 2009 (Study of Houston Atmospheric Radical Precursors campaign) and in 2011 (Air Quality Research Program study). Both in 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Previous analyses of HCHO data in Houston have reached contradictory conclusions on whether most of the HCHO is primary, i.e., directly emitted (Rappengluck et al 2010, Buzcu Guven and Olaguer 2011, Olaguer 2013, Johansson et al 2014 or secondary, i.e., produced within the plume from alkene oxidation (Friedfeld et al 2002, Wert et al 2003, Parrish et al 2012, Zhang et al 2013. The distinction is important because primary HCHO would accumulate at night and photolyze in early morning, providing a source of radicals to initiate ozone formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of HCHO data in Houston have reached contradictory conclusions on whether most of the HCHO is primary, i.e., directly emitted (Rappengluck et al 2010, Buzcu Guven and Olaguer 2011, Olaguer 2013, Johansson et al 2014 or secondary, i.e., produced within the plume from alkene oxidation (Friedfeld et al 2002, Wert et al 2003, Parrish et al 2012, Zhang et al 2013. The distinction is important because primary HCHO would accumulate at night and photolyze in early morning, providing a source of radicals to initiate ozone formation.…”
Section: Resultsmentioning
confidence: 99%
“…HCHO columns over the Houston urban area peak at 1.4 × 10 16 molecules cm −2 near the Houston ship channel where major refineries and petrochemical industries emit large amounts of HRVOCs. Johansson et al (2014) previously reported HCHO columns in the channel of up to 2.4 × 10 16 molecules cm −2 from ground-based remote sensing in May 2009. Our mean column of 9.4 × 10 15 molecules cm −2 in the Houston-Galveston-Brazoria urban metropolitan area (HGB; figure 1, thin blue line) corresponds to a mean HCHO mixing ratio of 2.4 ppb for a 1.7 km deep PBL (Haman et al 2012).…”
Section: Methodsmentioning
confidence: 95%
“…The Solar Occultation Flux (SOF) method uses direct sunlight to determine vertically integrated concentrations of trace gases (Mellqvist et al, 2010;EPA Handbook, 2011;Johansson et al, 2014b;Kim et al, 2011;European Commission, 2015). The SOF method has been used on mobile platforms to measure ethene (de Gouw et al, 2009;Mellqvist et al, 2010;Johansson et al, 2014a, b), propane (Mellqvist et al, 2010;Johansson et al, 2014a, b) and alkanes including C 2 H 6 (Johansson et al, 2014b), C 2 H 4 and C 3 H 6 (Kim et al, 2011). De Foy et al (2007) used the SOF method stationary to measure alkanes and NH 3 , amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with wind measurements, mobile column measurements of trace gases have been shown to be very useful to constrain emission of trace gases from source regions by applying a mass conservation approach (e.g., Baidar et al, 2013b;Ibrahim et al, 2010;Johansson et al, 2014a, b;Mellqvist et al, 2010;Shaiganfar et al, 2011;Wang et al, 2012). Mobile column measurements from various platforms have previously been used to estimate nitrogen oxides (NO x ) emissions from cities (Baidar et al, 2013b;Ibrahim et al, 2010;Shaiganfar et al, 2011;Wang et al, 2012), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ) (Johansson et al, 2014a), and formaldehyde (HCHO) (Johansson et al, 2014b) from industries using the differential optical absorption spectroscopy (DOAS) (Platt and Stutz, 2008) technique and fugitive volatile organic compound (VOC) emissions from refineries (e.g., Mellqvist et al, 2010;Johansson et al, 2014a, b) using the solar occultation flux (SOF) (Mellqvist et al, 2010) method. The DOAS method typically is limited to the UV-Vis wavelength region and uses scattered sunlight; while the SOF method uses direct sun observations in the mid-IR wavelengths.…”
Section: Introductionmentioning
confidence: 99%